VALUES IN SERAT CEMPORET BY RADEN NGABEHI RANGGAWARSITA - Puspitasari , Rian; Liharyanti, Noni; Lastini, Lastini (Jurnal Ilmu Bahasa, Sastra dan Pengajarannya, 2022)
The purpose of the research is to describe the values in Serat Cemporet by R. Ng. Ranggawarsita, especially pupuh I to pupuh XVI and describe the relevance of the values in today’s life as well as socio-cultural changes in today’s society. The type of research in this study uses a content analysis model. This research uses Tarigan and Notonegoro’s theory of literary values which then limits the research by examining ethical values, social values, moral values, religious values and cultural values. The subject of this research is the manuscript of Serat Cemporet by R. Ng. Ranggawarsita that has been transliterated and translated by Sudibjo Z. Hadisutjipto which is kept in Radya Pustaka Surakarta museum. The research data are the lines of tembang macapat in Serat Cemporet by R. Ng. Ranggawarsita. In the data collection technique, library technique was used, followed by listening and note-taking techniques. In the data analysis technique, the content analysis model was used. The result of this research shows that the stanzas in pupuh I to pupuh XVI contain life values. The life values include (1) Religious values: belief in destiny, gratitude, resignation; (2) Ethical values: speech, manners or manners; (3) Moral values: patience, keeping promises, wisdom, humility, not easily discouraged; (4) Social values: helping, love, loyalty, solidarity; (5) Cultural values: culture in oneself, culture in society. There is a form of relevance of values to life today, as well as socio-cultural changes that existed in ancient times and today